Plasma‐Activated Solutions Mitigates DSS‐Induced Colitis via Restoring Redox Homeostasis and Reversing Microbiota Dysbiosis - Tuanhe Sun; Kaijie Ren; Guimin Xu; Rulan Ma; Xueni Wang; Tianhao Min; Xin Xie; Anbang Sun; Yuyi Ma; Haonan Wang; Yong Zhang; Kun Zhu; et al. (Advanced Science, 2023)
Abstract Ulcerative colitis is a chronic disease that increases the risk of developing colorectal cancer. Conventional medications are limited by drug delivery and a weak capacity to modulate the inflammatory microenvironment. Further, gut microbiota dysbiosis caused by mucosal damage and dysregulated redox homeostasis leads to frequent recurrence. Therefore, promoting mucosal healing and restoring redox homeostasis is considered the initial step in treating ulcerative colitis. Plasma‐activated solutions (PAS) are liquids rich in various reactive nitrogen species (RNS) and reactive oxygen species (ROS) and are used to treat multiple diseases. However, its effect on ulcerative colitis remains to be examined. Therefore, using a DSS‐induced mice colitis model, it is found that PAS has the potential to treat colitis and prevent its recurrence by promoting intestinal mucosal repair, reducing inflammation, improving redox homeostasis, and reversing gut microbiota dysbiosis. Further, an equipment is designed for preparing PAS without using nitrogen; however, after treatment with the Nitro‐free PAS, the therapeutic effect of PAS is significantly weakened or even lost, indicating that RNS may be the main mediator by which PAS exerts its therapeutic effects. Overall, this study demonstrates the treatment of ulcerative colitis as a novel application of PAS.